2022
DOI: 10.24198/ijpst.v1i1.30486
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Moisturizing Lotion Containing Silkworm (Bombyx mori L.) Sericin Nanoparticles

Abstract: Sericin as one of two main proteins in silkworm (Bombyx mori L.) cocoons was found to have the ability to increase skin moisture in cosmetics. The objective of this study was to determine the optimal formula of sericin nanoparticle lotion and the effectiveness of sericin nanoparticle lotion. The formation of sericin nanoparticles was mainly carried out by mixing and stirring mechanism using urea as a crosslinking agent. Temperature and stirring speed were fixed, while stirring duration were varied. Optimal ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Silk, a protein biomaterial, has interesting qualities which suggest that it can be used as a natural sunscreen agent. Studies have shown that Bombyx mori silk contains bioactive compounds with UV blocking and antioxidant abilities, which may contribute to the prevention of photoaging (Hidayat et al, 2022;K. Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Silk, a protein biomaterial, has interesting qualities which suggest that it can be used as a natural sunscreen agent. Studies have shown that Bombyx mori silk contains bioactive compounds with UV blocking and antioxidant abilities, which may contribute to the prevention of photoaging (Hidayat et al, 2022;K. Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%